2007
DOI: 10.17816/ecogen5237-43
|View full text |Cite
|
Sign up to set email alerts
|

Chemosignaling in Cba and C57bl/6 Mouse Strains Is Modified by Stress

Abstract: Chemosignaling is widespread among animals as tool for regulation of synecological interactions. Evolutional conservatism of such signaling allows us to suggest that same chemosignals play an important role in different animal species including human beings. Aversion/attraction of mouse pheromone 2,5- dimethylpyrazine (2,5-DMP) and 2,3-dimethylpyrazine (2,3-DMP) for CBA and C57BL/6 mice was studied in T-maze. It is shown that intact males and females of both strains under choice condition prefer 2,3-DMP to wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Thus two factors can be specified that determine biological activity of olfactory chemosignals in house mice: (1) relative position of methyl radicals in the pyrazine ring, which was shown earlier [10,11]; (2) the lateral chain structure revealed in the present work by using the metaphase analysis.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Thus two factors can be specified that determine biological activity of olfactory chemosignals in house mice: (1) relative position of methyl radicals in the pyrazine ring, which was shown earlier [10,11]; (2) the lateral chain structure revealed in the present work by using the metaphase analysis.…”
Section: Discussionmentioning
confidence: 68%
“…2,3-Dimethylpyrazine (2,3-DMP) has been shown to be attractive, while 2,5-DMP aversive both to males and to females of CBA mice used as test animals [11]. Preliminary data show that 2-carboxy-5-methylpyrazine (CMP) is also aversive to test animals.…”
Section: Introductionmentioning
confidence: 99%
“…The excretion of 2,5-dimethylpyrazine (DMP) in mouse urine is adrenal dependent (Ma et al, 1998). In CBA mice it has been shown that tester males and females avoid DMP in a T-maze (Daev et al, 2007). Smelling DMP also induces immune suppression in mice: the quantity of antibody-producing cells is reduced as under physical stress, and the chromosome aberration level in bone marrow dividing cells is increased (Daev et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%